Benefits of powered standing wheelchair devices for adolescents with Duchenne muscular dystrophy in the first year of use. (3rd July 2020) - Bayley, Klair; Parkinson, Stephanie; Jacoby, Peter; Cross, Donna; Morris, Sue; Vorster, Nitamarie; Schofield, Cara; Kava, Maina; Siafarikas, Aris; Evans, Kerry; Gaynor, Odette; Chiu, Linda; et al.
Abstract : Aim: Poorer physical and mental health often accompany loss of walking in Duchenne muscular dystrophy. This study assessed the impacts of powered wheelchair standing device (PWSD) use on muscle and joint pain, joint angles when standing and mental health in adolescents with Duchenne muscular dystrophy. Methods: Fourteen adolescents and parents participated in a stepped wedge design study over 12 months. During a baseline and intervention period, adolescents described pain and mental health, and parents reported their child's mental health. Video data were collected to measure hip, knee and ankle joint angles in the preferred standing position. Results: Compared with baseline and adjusting for covariates, standing wheelchair use was associated with no change in muscle or joint pain or videoed joint angles in standing. Child‐reported Strengths and Difficulties total scores decreased (coefficient −3.1, 95% confidence interval −4.6, −1.5); and parent‐reported Personal Adjustment and Role Skills Scale total scores increased (coefficient 7.9, 95% confidence interval 3.3–12.5). Conclusions: PWSD use was associated with maintenance of musculoskeletal status and advantages to mental health. Long‐term observations are necessary to improve understanding of how to support wellbeing in adolescents with Duchenne muscular dystrophy.